Angiokeratoma in Fabry Disease: Diagnostic but not Treatment Effectiveness Marker - Roganovic, Jelena; Barisic, Ingeborg; Jonjic, Nives; Fumic, Ksenija; Dordevic, Ana (Global Journal of Medical and Clinical Case Reports, 2014)
Introduction: Fabry disease (FD) is a rare metabolic disorder that leads to severe morbidity and premature mortality as a result of cardiac, renal or cerebrovascular complications. Enzyme replacement therapy (ERT) has been shown to provide clinically important benefits, and treatment is likely to alter the natural history of FD. Case Report: The authors describe a 7-year-old boy with FD. Vascular skin lesions were very helpful in guiding appropriate investigations leading to prompt diagnosis. Because of multisystem involvement, including signs of nephropathy, ERT was started. The boy showed catch-up growth with skeletal maturation, and albuminuria reversed. However, angiokeratomas increased in size and number. Conclusion: The most recognizable early physical sign of FD is angiokeratoma, which can play a critical role in the detection of the disease. However, there is no compelling evidence that angiokeratoma can serve as a surrogate marker for the course of the disease or the efficacy of ERT.